French Immersion Teen Camp : Feasibility Study - Newcombe, Vanessa; Roberts, Carla; Griffin, Emily (Coasters Association, 2008)
Living in such an isolated area such as, the Lower North Shore, there is a lack of activities for all ages, but more so for the adolescent age. There are very few activities on the Lower North Shore that directly focuses on teenagers, so teens resort to other activities that result in social problems (i.e. drinking, drugs, vandalism, etc…). Therefore, a French Immersion Teen Camp would provide teenagers with activities and a program that is especially designed for them. Teenagers could have a chance to get away from the social problems and into a program that will nurture and develop a safe and healthy environment in which the teens can improve their health and obtain skills that will assist them in their future lives and also promote and develop their French as a Second Language skill.